Numerical Simulation on the Influence of Bridge Construction on River Flood Control in a Bottleneck Reach - Han, Jianqiao; Wang, Honglei; Luo, Han; Duan, Wenzhong (ITB Journal Publisher, LPPM ITB, 2018)
Bottleneck reach regions with narrow and deep cross sections prevent sediment transport and weaken flood control capacity. In addition, bridge constructions can exacerbate the risk of flooding in these areas. In this study, the Longhai Railway Extension Project at the Xianyang reach of the Weihe River in China was selected as a typical object. A horizontal 2-D numerical model was used to assess the effects of three engineering plans on flood discharge capacity under three flood frequencies. Plan 1 was designed to include building a new bridge, demolishing the three original bridges and dredging a single section of the channel. Plan 2 was the same as Plan 1, except for the compound sections. Plan 3 was designed with the four bridges coexisting and no dredging projects carried out. The results indicated that Plan 3 will increase the water level by 0.2-0.3 m in the upstream reach. The cross-sectional area was approximately 370 m2 larger under Plan 1 than under Plan 2. Water levels of 300-, 100-, and 5-year flooding around the bridge were reduced by 0.9, 0.9, and 0.6 m, respectively. To improve flood control capacity, an effective dredging project must be executed to widen the river and reduce the water stage in the bottleneck reach where the bridge is constructed.